Boromir’s Defense Mechanism In Lord of The Rings: Fellowship of The Ring - Sukma Eka Satya Ginalih; Nungki Heriyati (STKIP PGRI Tulungagung, 2020)
The objective of this research is to analyze Boromir’s defense mechanism and his characterization. This research applies several theory and method which encompasses characterization, psychoanalysis, and defense mechanisms. It is also aims to examine the types of defense mechanism used by the character. Data are collected from scenes of the film, dialogues, gestures, responses and facial expressions of the character. The field of the study are around the scene of the films of which the character appeared. Some limited history are also studied, collected from the film and biography from other sources. The result of the research shows that the character is considered as a representation of psychological state of human being. It shows the way human defend him/herself when facing problem. In the analysis, the character uses several defense mechanisms which is Reaction formation, Denial, and Displacement that made the character resist the tempation to harm his companion and being reckless.